Lemarchand, Marie-Jose, Ed. & Trad. 2000: Cristina de Pizan: la ciudad de las damas - Hernández Pérez, María Beatriz (SELIM. Journal of the Spanish Society for Medieval English Language and Literature, 2019)
Sin resumen